Anisotropy of the electron effective mass in rutile SnO2 determined by infrared ellipsometry. Issue 1 (4th October 2013) - Feneberg, Martin; Lidig, Christian; Lange, Karsten; White, Mark E.; Tsai, Min Y.; Speck, James S.; Bierwagen, Oliver; Goldhahn, Rüdiger
Abstract Generalized infrared spectroscopic ellipsometry (GIRSE) was applied to Sb‐doped rutile SnO2(101) films grown by plasma‐assisted molecular beam epitaxy (PAMBE). Coupled longitudinal‐optical (LO) phonon–plasmon (LPP) modes for the two principal polarization directions of the optically anisotropic SnO2 were identified and their frequencies were determined as a function of electron concentrations obtained by Hall effect measurements. The analysis of these modes yielded very accurate values for the plasma frequencies and finally the anisotropy of the electron effective masses as a function of carrier density. Comparison to Hall effect electron concentrations yielded a non‐parabolicity of the conduction band.